The future of malls : was decline inevitable? - Rosenthal, Jean, active 2019; Williams, Anna, active 2019; Colon, Brandon; Park, Robert, active 2019; Goetzmann, William N.; Helfand, Jessica (London : Yale School of Management, 2019)
The Cross County Shopping Center was in Yonkers, in the suburbs of New York City. Built in 1954 as one of the first open air shopping malls and renovated in 2011, the Center captured many of the challenges facing American suburban shopping centers in the 21st century. It was large, a "super-regional," with a total size of over a million square feet. The Cross County had had a successful history, but its future, along with that of other U.S. malls, was far from certain.
Originally published in : Rosenthal, J., Williams, A., Colon, B., Park, R., Goetzmann, W., & Helfand, J. (2019). The Future of Malls: Was Decline Inevitable?. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol12.cases.som.yale.edu/future-malls.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cross County Shopping Center (Yonkers, N.Y.) -- Case studies; Shopping malls -- Case studies